2011
DOI: 10.4103/0975-7406.84432
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal ultrasonography in first trimester of pregnancy and its comparison with transabdominal ultrasonography

Abstract: Objectives:Examination of pregnant women in the first trimester with transvaginal ultrasonography with the aim to study various fetal development markers, e.g., gestation sac, yolk sac, fetal heart motion, CRL length, and fetal anatomy in both normal and abnormal pregnancies. Comparative evaluation of transvaginal ultrasonography vis-à-vis transabdominal scanning in the study of first trimester of pregnancy and its complications. To assess the relative merits and demerits of transvaginal ultrasonography in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 8 publications
3
19
0
Order By: Relevance
“…Kaur et al by their similar study, found the mean sac diameter and crown rump length measured by transvaginal and abdominal sonography in early pregnancy to be almost identical. 8 This was found similar to our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Kaur et al by their similar study, found the mean sac diameter and crown rump length measured by transvaginal and abdominal sonography in early pregnancy to be almost identical. 8 This was found similar to our study.…”
Section: Discussionsupporting
confidence: 93%
“…In the abnormal pregnancy TVS provided more information in 11 cases (64.9%), which included detection of embryonic demise or yolk sac. 8 These findings were found similar to our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Formula B has a higher EP than formula A and P. EP formula B is also higher than the results of Sugita et al [5] research by using the same method. The EP is also higher than EP rivastigmin coated with chitosan nanoparticles modified with STPP [18]. This study shows consistent results from Sugita et al [5] studies, formula B is a formula with physical properties better than formula A and P, but all of three formulas can be developed further as a candidate for ketoprofen drug coating.…”
Section: A B and P Formula Propertiessupporting
confidence: 89%
“…Knowledge of the ultrasound appearances of normal early pregnancy development and a good understanding of its pitfalls are essential for the diagnosis and management of early pregnancy failure. 3 Ultrasound imaging has rapidly replaced all other techniques used to study normal human development in the first trimester, and ultrasound features of the early gestational sac have corroborated anatomical studies showing that the first structures to appear are the coelomic cavity and the secondary yolk sac. 4 No single ultrasound measurement of the different anatomical features in the first trimester has been shown to have a high predictive value for determining early pregnancy outcome.…”
Section: Introductionmentioning
confidence: 99%